"There's nothing here": Perspectives from rural parents promoting safe active recreation for children living with autism spectrum disorders. (August 2021) - Shannon, Crystal A.; Olsen, Lise L.; Hole, Rachelle; Rush, Kathy L.
Highlights: Recreational participation by children with autism is important for healthy development. Research is limited on parents' experiences promoting safe recreational participation, particularly in rural settings. Parents have complex safety concerns linked to their child's recreational participation. Safe spaces and training of recreation personnel are required to better support children with autism. Abstract: Background: Children with autism spectrum disorder (ASD) and their families experience challenges and barriers at multiple levels that influence their activity participation. The purpose of this study was to develop understanding about factors influencing how families can promote safe, active recreation for their children 3–12 years living with ASD across rural settings and how supports for these families can be enhanced. Methods: This qualitative study used an interpretive descriptive approach. Twelve in-depth, semi-structured interviews with parents of children with ASD were conducted. Data was analyzed thematically. Results: Four main themes emerged: 1) ASD specific child vulnerabilities impeding safe recreation. 2) Importance of safe outdoor spaces in rural settings for children with ASD. 3) Diverse parent strategies to address risks and needs. 4) Perceived needs for training of recreation providers. Conclusion: Findings highlight family-centred priority issues including parental safety concerns related to elopement and risk of injury linked to environmental and outdoor hazards prominent in rural settings. Autism awareness and recreational training is needed and could incorporate collaborative development of child specific safety plans to foster inclusive opportunities. Program planners can use this information to encourage policy making to aid families' safe activity participation.